MicroRNAs in parathyroid physiopathology. (15th November 2017) - Vaira, V.; Verdelli, C.; Forno, I.; Corbetta, S.
Abstract: Parathyroid glands regulate calcium homeostasis through synthesis and secretion of parathormone (PTH). They sense the extracellular calcium concentration through the G-protein coupled calcium sensing receptor (CASR) and release PTH in order to preserve calcium concentration in the physiological range. Tumors of the parathyroid glands are common endocrine neoplasia associated with primary or secondary/tertiary hyperparathyroidisms. Small non-coding RNAs are regulators of gene expression able to modulate hormone synthesis, hormone release and endocrine cell proliferation. In this scenario, microRNA (miRNA) expression profiles have been investigated in parathyroid tumors, while miRNAs are involved in hypocalcemia and uremia-induced PTH release from normal parathyroid cells. Here we reviewed data about the role of miRNAs in the regulation of: 1) PTH synthesis and secretion; 2) CASR expression; 3) parathyroid cell tumorigenesis. Though studies about miRNAs in parathyroid gland pathophysiology are limited, they contribute in elucidating regulatory pathways involved in PTH release and parathyroid cell tumorigenesis. Highlights: MicroRNAs are involved in the modulation of PTH release from normal parathyroid cells in response to hypocalcemic stimuli. MicroRNAs are potentially involved in regulation of calcium sensing receptor gene expression. MicroRNAs profiling is perturbed in parathyroid tumors with respect to normal glands. Deregulation of microRNAs belonging to imprinted genomic regions, C19MC and GNAS loci characterizes parathyroid carcinomas. Parathyroid benign and malignant lesions show distinct microRNAs footprints.